Intermediate Algebra (6th Edition)

Published by Pearson
ISBN 10: 0321785045
ISBN 13: 978-0-32178-504-6

Chapter 7 - Section 7.7 - Complex Numbers - Exercise Set: 11

Answer

-6i

Work Step by Step

$-\sqrt(-36)=-(\sqrt(-36))=-(\sqrt (36\times-1))=-(\sqrt 36\times\sqrt -1)=-(6i)=-6i$ We know that $\sqrt -1=i$, because $i^{2}=-1$. In this case, we are finding the opposite of $\sqrt (-36)$.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.